MEMBANGUN HUBUNGAN YANG BAIK DAN SEHAT DI PANTI ASUHAN YASIBU KOTA MALANG - Surya Marcello Pangestu; Siti Nur Khodijah; Syafana Auliyah Kholiqin (FIP UNIRA MALANG, 2026)
Children living in orphanages are at risk of experiencing obstacles in social and emotional development due to limited access to consistent caregiving relationships. This condition highlights the need for systematic efforts to foster positive and healthy relationships as a foundation for developing a sense of security and social interaction skills in children. This community service activity aimed to strengthen social relationships among children aged 5–12 years at YASIBU Orphanage, Malang City. The method employed was a descriptive qualitative approach implemented through introductory activities, material delivery, group games, and reflection sessions. The participants consisted of 18 children residing in the orphanage. Data were collected through observations of children’s engagement and responses throughout the activities. The results indicated increased participation, improved cooperation skills, greater confidence in communication, and more open emotional expression. This activitycontributes to supporting children’s social and emotional development and to creating safe and supportive interaction experiences within the orphanage environment.